Critical Review on Hamsa Pottali Rasa-A Herbo-mineral Formulation - Pooja B; Seema M B; Surekha S Medikeri (RGUHS Journal of AYUSH Sciences)
Ayurveda often mentions use of herbal and herbo-mineral formulations in various disease conditions. In classics we discover ayurveda formulations with the same name in several books. While they occasionally share the same components and indications they also have different ingredients and indications despite sharing the same name. The action of a formulation depends on various factors such as ingredients and their pharmacological actions time of collection method of preparation dose route of administration and adjuvants. Therefore it is essential to comprehend the formulations before using them for medicinal purposes or further research. Hamsa Pottali Rasa is one such example. Four formulations are available in the literature in the name of Hamsa Pottali Rasa. All four references are indicated in grahani and mostly act on digestive and respiratory conditions. In this study an effort was made to compile and analyze the four Hamsa Pottali Rasa formulations from different texts and also to provide insight into their components dosages indications modes of action and applications.